Population Development of Several Species of Ants on the Cocoa Trees in South Sulawesi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2010)
Several species of ants with different behavior have been found in cocoa plantations and their behavior is important to be considered because it might be correlated with the degree of protection of cocoa plant from cocoa pests. The aim of this research is to manipulate and to develop ants population in environment, so they are able to establish permanently in cocoa trees. This research was conducted in Papakaju Regions Luwu Regency in Juli to November 2009. In this study, 10 cocoa trees with ants were sampled (each species of ant in 10 cocoa trees). A control of 10 tree samples without ant was also taken. In order to assess the abundance of ant population, it was grouped based on scoring, which score 1 for less than 20 ants, score 2 for 21–50 ants, score 3 for 51–200 ants, score 4 for 201–1000 ants, and score 5 for more than 1000 per tree. The results indicated that average of population score of the three ants species reached the highest population for the Oecophylla. smaragdina with average score 4.85 (>1000 ants), Dolichoderus thoracicus, with average score 3.90 (> 200 ants) and Crematogaster. difformis with average score 3.10 (>200 ants). This research indicated that three species of ants, Oecophylla smaragdina (weaver ant), Dolichoderus thoracicus (cocoa black ant) and Crematogaster difformis (cracking ant). in farmer cocoa plantations in South Sulawesi giving better performance against major pests of cocoa in particular cocoa pod borer (CPB). Key words: Ant Population, Oecophylla smaragdina, Dolichoderus thoracicus, Crematogaster difformis, artificial nest, cocoa.